Pemahaman GMIT dalam Pokok – Pokok Eklesiologi Gereja Masehi Injili di Timor (PPE GMIT) tentang Budaya Lokal, Ilmu Pengetahuan dan Teknologi berdasarkan Perspektif Glokalisasi - Nayuf, Henderikus (Institut Agama Kristen Negeri Toraja, 2023)
This paper focuses on the effort to interpret the relationship between the Evangelical Church of Timor (Gereja Masehi Injili di Timor – GMIT) and local culture, as well as GMIT and science and technology within the Ecclesiology Principles of GMIT. The aim is to understand and interpret the relationship between GMIT and culture, as well as GMIT's position in interpreting the advancements of science and technology, which are tangibly experienced through the force of globalization. This paper adopts a qualitative method with a phenomenological approach. This approach is used to comprehend how GMIT is confronted with both the force of globalization and the strengthening of local wisdom values within the GMIT region. The phenomenon of interest is whether GMIT rejects local and global cultures or accepts both and elaborates them as instruments of service. The conclusion drawn is that in order to interpret these two forces consciously adopted as foundations in the endeavors of GMIT through the Ecclesiology Principles, a new perspective is needed, namely